FAM105B Promotes Hepatocellular Carcinoma Progression and Metastasis by Activating the PI3K/AKT/MTOR Signaling Pathway and Inducing Epithelial-Mesenchymal Transition - Yang LL; Chen X; Tang ST; Huang KT; Ye GY; Wang JL (Journal of Hepatocellular Carcinoma, 2025)
Liu-Lin Yang,1,* Xing Chen,2,* Shao-Tong Tang,1 Kai-Ting Huang,1 Gui-Yan Ye,1 Ji-Long Wang1 1Department of Hepatobiliary Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China; 2Department of Ultrasound, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ji-Long Wang, Department of Hepatobiliary Surgery, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi, People’s Republic of China, Email wangjilong-yucheng@163.comBackground: Recurrence and metastasis are major contributors to poor prognosis in hepatocellular carcinoma (HCC), yet the mechanisms remain unclear. FAM105B, a specific deubiquitinating enzyme, is critical in various biological processes, including cancer progression. However, its role in HCC is not well understood.Methods: FAM105B expression in HCC patients was validated using public clinical datasets. Cox regression and Kaplan-Meier analyses assessed its association with clinicopathological features and prognosis. In vitro and in vivo experiments evaluated the effects of FAM105B on HCC cell proliferation and invasion. Its role in epithelial-mesenchymal transition (EMT) and the PI3K/AKT/MTOR pathway was analyzed via, Western blot, Reverse Transcription Quantitative Polymerase Chain Reaction (qRT-PCR), immunohistochemistry and immunofluorescence.Results: FAM105B was significantly upregulated in HCC tissues and cell lines. High FAM105B expression correlated with aggressive features and poorer overall survival (OS) and disease-free survival (DFS). Functional studies revealed that FAM105B overexpression promoted, while knockdown inhibited, HCC cell proliferation and invasion. Mechanistically, FAM105B induced EMT and activated the PI3K/AKT/MTOR pathway.Conclusion: FAM105B promotes HCC progression by inducing EMT and activating the PI3K/AKT/MTOR pathway, highlighting its potential as a therapeutic target and prognostic biomarker.Keywords: FAM105B, hepatocellular carcinoma, proliferation, invasion, EMT, PI3K/AKT/MTOR